Obesity and pituitary gland volume – a correlation study using three-dimensional magnetic resonance imaging. Issue 5 (October 2020) - Fehrenbach, Uli; Jadan, Anas; Auer, Timo A; Kreutz, Katharina; Geisel, Dominik; Ziagaki, Athanasia; Bobbert, Thomas; Wiener, Edzard
Purpose: Obesity has become a major health problem and is associated with endocrine disorders and a disturbed hypothalamic-pituitary axis. The purpose of this study was to correlate pituitary gland volume determined by routine magnetic resonance imaging with patient characteristics, in particular body mass index and obesity. Material and methods: A total of 144 'healthy' patients with normal findings in cerebral magnetic resonance imaging were retrospectively included. Pituitary gland volume was measured in postcontrast three-dimensional T1-weighted sequences. A polygonal three-dimensional region of interest covering the whole pituitary gland was assessed manually. Physical characteristics (gender, age, body height and body mass index) were correlated with pituitary gland volume. Multiple subgroup and regression analyses were performed. Results: Pituitary gland volumes were significantly larger in females than in males ( p <0.001) and young individuals (<35 years) versus middle-aged patients (35–47 years) ( p =0.042). Obese patients (body mass index ≥30) had significantly larger pituitary gland volumes than overweight (25<body mass index<30; p =0.011) and normal-weight (body mass index <25; p =0.005) patients. In males, pituitary gland volumes of body mass index subgroups showed significant differences ( p =0.038). Obese males had larger pituitary gland volumes than overweight patients ( p =0.066) and significantly larger volumes than normal-weight ( p =0.023) patients. Obese females also had larger pituitary gland volumes but without statistical significance ( p >0.05). Regression analysis showed that increased pituitary gland volume is associated with higher body mass index independent from gender, age and body height. Conclusion: Pituitary gland volume is increased in obese individuals and a high body mass index can be seen as an independent predictor of increased pituitary gland volume. Therefore, gland enlargement might be an imaging indicator of dysfunction in the hypothalamus-pituitary axis. Besides gender and age, body mass index should be considered by radiologists when diagnosing abnormal changes in pituitary gland volume.